2016
DOI: 10.1515/amm-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Transition Phases on Interface between Monocrystalline Fe and Cu Due to Mutual Solid-State Diffusion

Abstract: Interdiffusion between Fe (Armco) and Cu single crystals of similar orientation (around [110]) annealed at temperatures of 873 and 973K in air for 0.5 up to 4 h is studied. Formation of three phases different in their chemical composition has been observed: 1) oxide layer on Cu border (porous), 2) a layer rich in copper, iron and oxygen, 3) a layer of iron and oxygen with only small addition of Cu. All reactions of interface formation occurred in solid state. It was noted that oxygen plays an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Additionally, at any temperature, as the carbon content in the steel increased, the diffusion coefficient of Cu in the steel showed a gradually decreasing trend. M. Perek-Nowak et al studied the influence of oxygen on the diffusion between Cu and Fe at 600-700 • C under the action of 20 N extrusion force [23]. They found that oxygen appeared to have great effect on formation of the connection, and for the microstructure, the dark-grey layer consisted of iron oxide with small addition of copper atoms (bellow 2 at.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, at any temperature, as the carbon content in the steel increased, the diffusion coefficient of Cu in the steel showed a gradually decreasing trend. M. Perek-Nowak et al studied the influence of oxygen on the diffusion between Cu and Fe at 600-700 • C under the action of 20 N extrusion force [23]. They found that oxygen appeared to have great effect on formation of the connection, and for the microstructure, the dark-grey layer consisted of iron oxide with small addition of copper atoms (bellow 2 at.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the joined components is also limited, since metals applicable for components joined in this way should exhibit mutual solubility in the solid state. In spite of this, in some applications such as the manufacture of thermocouple joints, pressure welding is unrivalled [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%